Prevalence of HIV/AIDS in Nepal Army and its Dependants - Khatri, R; Roka, K (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: The Asia Pacific Region is currently at the “tip of iceberg” phase of the HIV/AIDS epidemic after African countries causing irreparable economic damage and undermining national and regional security if left unattended. HIV/AIDS remains a serious national concern and potential for epidemic relapse is high1. Continued vigilance is important. Study of the Prevalence of HIV/AIDS in Nepal Army (NA) and its dependants is based on the data collected from various sources to highlight the importance of ongoing measures plus the need of effective programs against HIV/AIDS control. Methods: This is a descriptive study and data are derived from February 1996 to March 2011 from the different sources. National Guideline for testing of HIV in Nepal, developed in 2003 was used for the diagnosis of the cases by blood tests in Birendra Hospital, Chhauni. Results: Total of 116 cases was diagnosed HIV positive. Maximum number of HIV positive cases was diagnosed in the year 2010 as compared to other years since 1996 and for the year 2011 till the month of March. The positive cases diagnosed from army personnel in UN Mission and blood donation programs accounted for 0.02% and 0.09% respectively. And from the surgical patients in the army hospital, 0.18% cases were diagnosed positive. From the year 2006 to 2010, 0.38% cases were diagnosed as positive among the voluntary counselling and testing (VCT) volunteers. Conclusion: HIV is a threat to the army, behaviour change and prevention is the key and it needs to be adapted to the best. Intensive training, massive awareness programs and behavioural issues start at the recruit level and need to be reinforced prior and during deployment with regular monitoring of the soldiers activities. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6445 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 20-25